A review of vehicle inspection laws in Malaysia / Wan Ahmad Izzat Wan Kamil, Zulhilmi Mohamad Salleh and Mohd Khairi Anwar Jailani - Wan Kamil, Wan Ahmad Izzat; Mohamad Salleh, Zulhilmi; Jailani, Mohd Khairi Anwar (Faculty of Law, 2013)
This is a study on the issue of insufficiency on vehicle inspection laws in Malaysia with respect to the Road Transport Act 1987 (Act 333) and Road Transport Rules 1995 as well as inefficacy of the laws from the aspect of environment based on Environmental Quality Act 1974. The aims of the research are to identify the relevant laws on vehicle inspection in Malaysia and to analyse the inefficacy of vehicle inspection in regards of vehicle emission. The methods used in this research were semi-structured interviews, extracting information from journals, articles and report, which were used to obtain information of other countries which are related to our issues. The analysis of the research found that there exist the needs to implement vehicle inspection laws on private vehicle. Currently in Malaysia, only commercial vehicles are made mandatory to undergo periodic inspection, whilst private vehicles are to have inspection only on a few circumstances, which is upon modification of the private vehicle and upon a transfer of ownership of the private vehicle; however these two inspections seldom occurs. Vehicle inspection helps in determining the defects of a vehicle, and to ensure the vehicle is in a roadworthy condition to be used on the road. In addition, the lack of vehicle inspection leads to another issue, which is the emission of hazardous substances by the unmaintained vehicles. This paper highlight the need to have vehicle inspection in order to maximise the safety of drivers and road users by maintaining vehicles to always be in a roadworthy condition, plus, to ensure vehicle to emit clean emission for the benefit of the society and environment.